Investigation of validity and reliability works in postgraduate mathematics theses that adopt qualitative research in Turkey: Functions of data collection tool - (:unkn) unknown (E D P SCIENCES, 2016)
In this research, master and doctorate thesis which adopts qualitative method in mathematics education studies in Turkey are thoroughly inspected in terms of their validity and reliability, thus the research has a case study as a research model. From Thesis Web site by Council of Higher Education, 119 master thesis which are published and contains both primary and secondary mathematical studies and 27 doctorate thesis are analysed by using document analysis technique and data is resolved by means of content analysis. It was seen in almost more than half of these theses in which reliability and validity are done, that in addition to the credibility, transmissibility, consistency and confirmability strategies that is used for qualitative paradigm, Statistical calculations are also used in regards of quantitative paradigm. Also, in most of the scale development and adaptation works, language validity technique was not used and in almost half of them, it was observed that strategies such as test works were not employed. In this case, it shows that Reliability and Credibility works remains unfulfilled and awareness of analysis strategies that are caused by scale differences remains low.